EXTENSION ACTIVITIES PROVIDED TO RICE FARMERS IN RAISING THE AWARENESS FOR COMPOST MANUFACTURE IN AL-DIWANIYAH PROVINCE - Al-Salhi, A. T. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to determine extension activities provided to rice farmers in raising the awareness for compost manufacture in Al-Diwaniyah province and investigate the level of awareness of rice farmers in the field of compost manufacturing, as well as the problems facing farmers when manufacturing compost, mythology a questionnaire design to collect data from rice farmers during 2018 . The research society consisted of the agricultural departments of the directorate of Agriculture in Al Diwaniyah province. A random sample was taken from rice farmers related to the agricultural departments in the Directorate of Agriculture with their (632) farmers, The results of this study inculcated that the level of awareness for the farmers in the manufacture of compost, The average tends to weak in their awareness, The role of the agricultural extension has also just through extension seminars, which is considered one of the most extension activities were used to rice farmers of compost manufacturing, In addition, there is an absence of workers in the field of composting of rice residues, It could be to pay adequate attention to the rice crop as a strategic crop through the utilization of its waste and the elimination of environmental pollution that occurs as a result of burning those waste.